Answer:
(x, y) = (4, -3)
Step-by-step explanation:
I like a graphing calculator for most 1- and 2-variable problems.
__
Here, it looks convenient to use substitution: solve the first equation for x and use that in the second equation.
x = -2 -2y
5(-2 -2y) -3y = 29 . . . . substitute for x
-10 -10y -3y = 29 . . . . eliminate parentheses
-13y = 39 . . . . . . . . . . . collect terms, add 10
y = -3 . . . . . . . . . . . . . . .divide by -13
x = -2 -2(-3) = 4 . . . . . . use the equation for x to find x
(x, y) = (4, -3) . . . . the solution